A web tool for STORET/WQX water quality data retrieval and Best Management Practice scenario suggestion. (1st March 2015) - Park, Youn Shik; Engel, Bernie A.; Kim, Jonggun; Theller, Larry; Chaubey, Indrajeet; Merwade, Venkatesh; Lim, Kyoung Jae
Abstract: Total Maximum Daily Load is a water quality standard to regulate water quality of streams, rivers and lakes. A wide range of approaches are used currently to develop TMDLs for impaired streams and rivers. Flow and load duration curves (FDC and LDC) have been used in many states to evaluate the relationship between flow and pollutant loading along with other models and approaches. A web-based LDC Tool was developed to facilitate development of FDC and LDC as well as to support other hydrologic analyses. In this study, the FDC and LDC tool was enhanced to allow collection of water quality data via the web and to assist in establishing cost-effective Best Management Practice (BMP) implementations. The enhanced web-based tool provides use of water quality data not only from the US Geological Survey but also from the Water Quality Portal for the U.S. via web access. Moreover, the web-based tool identifies required pollutant reductions to meet standard loads and suggests a BMP scenario based on ability of BMPs to reduce pollutant loads, BMP establishment and maintenance costs. In the study, flow and water quality data were collected via web access to develop LDC and to identify the required reduction. The suggested BMP scenario from the web-based tool was evaluated using the EPA Spreadsheet Tool for the Estimation of Pollutant Load model to attain the required pollutant reduction at least cost. Highlights: The web-based tool allows collecting water quality data via web access. The tool identifies the required pollutant reduction for each flow regime. The tool suggests a BMP scenario by annual costs and efficiencies of BMPs.